Comparison of Additional Working Hours and Additional Labor Based on the Output Value of Construction Projects - Nuriardani, Gati; Kamandang, Zetta Rasullia (CIVED, 2023)
Quality, time, and cost are three important elements in the project and are interrelated where in its implementation problems can arise that are very likely to occur. One of them is delay. This delay problem also occurs in the Hospital Building Construction Project. In order to find a solution to the problem, this research uses two stages of analysis, namely Earned Value Analysis and Project Crashing on delays experienced by the project in week 17. The results of calculations using the Earned Value Analysis method obtained the value of Schedule Variance (SV) -Rp 146,450,657.32; Schedule Performance Index (SPI) 0.6688; Estimate Temporary Schedule (ETS) 48 weeks; and Estimate All Schedule (EAS) 65 weeks. So, the project that is planned to be completed in 49 weeks is predicted to experience a delay of 16 weeks. Furthermore, scheduling adjustments and analysis of the series of activities carried out with the help of Microsoft Project to determine the critical path. Project Crashing in this study was carried out by comparing two alternatives, namely by adding 4 hours of work (overtime) and increasing the workforce by 30%. Both alternatives can reduce the duration of work for 26 days. The cost required from the acceleration alternative by adding overtime hours is IDR 30,850,351,655.73 with an efficiency of -0.6%. For the alternative of additional labor requires a cost of Rp 30,572,882,563.04 with an efficiency of 0.3%.